The Implementation of Hybrid Learning in EFL International Classroom - Sofiyah Andaningrum; Hanif Nurcholish Adiantika; Susilawati (National Conference on Language, Education, and Technology Proceeding, 2023)
This research focused on the Implementation of Hybrid Learning itself. Document analysis was one of the qualitative research methodologies used in this study. The location chosen for this study was an EFL international class that offers hybrid learning. The implementation of the hybrid learning model was carried out in academic year 2021/2022. The video recordings of the hybrid class were used in this study as documents. The author ran three tests in the documentation checklist to obtain results. It was carried out to investigate if hybrid learning could be utilized in the classroom. After doing documentation checklist and sharing questionnaire the results obtained turned out not to be fully learning done hybrid because there are some points not achieved.